Intervensi Kebijakan Moneter Terhadap Investasi Portofolio: Kasus Indonesia dan Amerika Serikat - Nanda Alfarina; Hasdi Aimon (Universitas Negeri Padang, 2020)
This study aims to determine the effect of monetary policy measured by the central bank’s policy rate (X1) on portfolio investment (Y) in Indonesia and United States in the long run. The data used are secondary data seouced from SEKI BI, FRED The FEd, coinmarketcap.com, and investing.com, with the VECM (Vector Error Correction Mechanism) analysis methode. The study show The study shows the differences between the results that occur in Indonesia and the United States. The policy interest rate has a significant positive effect on portfolio investment in the long run in Indonesia, while in the United States the interest rate in the long run has a significant negative effect on portfolio investment. The difference in research results between the two countries shows the need for different treatment for monetary authorities in encouraging portfolio investment.